Role of lubricant with a plasticizer to change the glass transition temperature as a result improving the mechanical properties of poly(lactic acid) PLLA - Hatem R Alamri; Ahmed M El-hadi; Saeed M Al-Qahtani; Hasan S Assaedi; Abdullah S. Alotaibi (Materials Research Express, 2020)
Poly (lactic acid) (PLLA) is the best important bioplastics derived from renewable resources like blackstrap molasses (sugar beet, date palm and sugar cane). PLLA is brittle and has a low elongation at break, which hinders its applications in the industry. One method to solve this problem is to improve its mechanical properties by adding plasticizers. The PLLA blends were prepared at first by solution blending as a solvent casting method and then melting using a hydraulic hot press. PLLA was blended with a plasticizer (GMS/TA) to obtain a higher ductile of PLLA. The addition of lubricant and plasticizer (GMS/TA) leads to reduce the glass transition temperature (T _g ), melting point (T _m ), and the cold crystallization temperature (T _cc ) in PLLA blends. The mechanical properties of PLLA have been investigated. The results indicated compatibility between PLLA and additives. The elongation at the break of the PLLA blend is stretched 270% with a tensile strength of 16 MPa. The addition of lubricant with the plasticizer leads to sliding the chain of PLLA, which causes to increase the strain. The physical blending has been demonstrated to be an effective technique to obtain an environmentally friendly PLLA blend with good mechanical properties, therefore it can be used in the food packaging sector.